Characterisation and Strength Activity Index of Eco-Processed Pozzolan - Bernard, Abraham Henry; Rizalman, Ahmad Nurfaidhi (IIUM Engineering Journal, 2025)
Eco-processed pozzolan (EPP) is a newly emerging pozzolanic material produced from the extraction, refinement, and calcination of spent bleaching earth. Due to its pozzolanic characteristics, EPP is a novel interest in the material sustainability of concrete technology in Malaysia today. However, there is still a lack of studies on how much EPP replacement fulfills the minimum requirements of 75% of the value of the strength activity index (SAI) as specified in the ASTM C618 standard. This study investigated the chemical, physical, mineralogical, and microstructural properties of EPP. The results revealed that EPP fulfilled the criteria as a class N pozzolan as per ASTM C618. According to the XRD result, the mineralogical data suggest that the OPC has a high amount of alite and belite at 65.65% and 10.26%, respectively. In contrast, the EPP showed high amorphous silica at 64.28%. Based on the scanning electron microscopy (SEM) images, the EPP particles had a spherical and porous structure, which increased the amount of water required for the mortar containing EPP. This study also examined EPP's strength activity index (SAI) at 10%, 20%, 30%, 40%, 50%, and 60% as partial cement replacement. The results indicated that the SAI was reduced with high EPP replacement percentages due to lower CaO content. The 28-day SAI value satisfied the minimum requirement of pozzolan as per ASTM C618 for cement replacement by up to 40%. In conclusion, EPP performed well as a cementitious supplementary material, with 10% and 20% being optimal replacements for cement. ABSTRAK: Pozzolan Terproses-Eko (EPP) merupakan bahan pozzolan yang baharu terhasil daripada proses pengekstrakan, penapisan dan pengkalsinan daripada tanah peluntur terpakai. Disebabkan ciri-ciri pozzolaniknya, EPP menjadi tarikan terbaru dalam teknologi bahan konkrit lestari di Malaysia hari ini. Namun, masih terdapat kekurangan kajian mengenai berapa banyak penggantian EPP yang dapat memenuhi keperluan minimum 75% nilai indeks aktiviti kekuatan (SAI) seperti yang dinyatakan di dalam ASTM C618. Kajian ini menyelidik sifat kimia, fizikal, mineralogi, dan mikrostruktur EPP. Dapatan kajian mendapati bahawa EPP memenuhi kriteria sebagai pozzolan kelas N mengikut ASTM C618. Menurut dapatan XRD, data mineralogi menunjukkan bahawa OPC mempunyai kandungan alite dan belite yang tinggi iaitu sebanyak 65.65% dan 10.26%, masing-masing. Manakala, EPP menunujukkan kandungan silika amorfus yang tinggi pada 64.28%. Berdasarkan imej pengimbas mikroskop elektron (SEM), zarah EPP mempunyai struktur sfera dan berliang, di mana ia meningkatkan jumlah air yang diperlukan untuk mortar yang mengandungi EPP. Kajian ini juga mengkaji SAI EPP pada 10, 20, 30, 40, 50, dan 60% sebagai penggantian separa simen. Dapatan kajian menunjukkan bahawa penurunan nilai SAI dengan peratusan penggantian EPP yang tinggi disebabkan kandungan CaO yang rendah. Nilai SAI pada 28 hari memenuhi syarat minimum pozzolan mengikut ASTM C618 bagi penggantian simen sehingga 40%. Kesimpulannya, EPP berprestasi baik sebagai bahan tambahan simen, dengan 10% dan 20% sebagai penggantian simen yang optimum.